BRAND EQUITY SUSU CAIR UHT DAN PENGARUHNYA PADA PURCHASE INTENTION - Dharmawan Santoso; Mukhammad Najib (Jurnal Manajemen & Agribisnis, 2015)
Based on the Top Brand Survey of liquid milk products of 2012–2015, the rank of Frisian Flag has decreased since 2014. The objectives of this study were to 1) analyze the brand equity of Ultramilk, Indomilk, Frisian Flag, Milo and Bear Brand  and influences of brand equity on purchase intention for the UHT milk products. The descriptive analysis, Cochran test, semantic differential scale, and multiple-linear regression were used in the data analysis. As many as 105 respondents were involved in this study and selected by a purposive sampling method. The results showed that 1) Ultramilk is the top of mind and has five brand image associations, and it has attributes of food safety and healthy and good taste with extremely good scales. Bear Brand has attributes of food safety and complete nutritional content, and Milo has the best pyramid of loyalty, and 2) Brand equity simultaneously has a significant influence on purchase intention. However, in partial, the elements of brand equity that have significant influences on purchase intention include brand association and brand loyalty. Keywords: brand equity, Giant, purchase intention, milk, UHTABSTRAKTop Brand Survey 2012-2015 menunjukkan bahwa Frisian Flag mengalami penurunan peringkat dalam Top Brand Index produk susu cair. Penelitian ini bertujuan untuk menganalisis brand equity susu cair UHT Ultramilk, Indomilk, Frisian Flag, Milo dan Bear Brand beserta pengaruh brand equity pada purchase intention. Pengolahan data dengan menggunakan analisis deskriptif, uji cochran, skala semantic differential, dan regresi linier berganda. Responden dalam penelitian ini berjumlah 105 orang dengan metode penarikan contoh purposive sampling. Hasil penelitian menunjukkan bahwa 1) Ultramilk menjadi top of mind serta memiliki jumlah asosiasi pembentuk brand image terbanyak dari merek lainnya; kesan kualitas produk aman menyehatkan dan rasa enak berskala sangat baik dimiliki Ultramilk, sedangkan Bear Brand yaitu  produk aman menyehatkan dan kandungan gizi lengkap; Milo memiliki piramida loyalitas terbaik dari merek lainnya, 2) Secara simultan, brand equity berpengaruh signifikan terhadap purchase intention, namun secara parsial hanya elemen brand association dan brand loyalty yang berpengaruh signifikan terhadap purchase intention. Kata kunci: brand equity, Giant, purchase intention, susu, UHT